Ecological impacts of fluridone and copper sulphate in catfish aquaculture ponds. (25th February 2016) - Jacob, Annie P.; Culver, David A.; Lanno, Roman P.; Voigt, Astrid
Abstract: Fluridone and copper sulphate are often used for controlling macrophytes and algae in aquaculture ponds. The present study examined the ecological effects of these chemicals on macrophyte, phytoplankton, and zooplankton biomass; plankton community structure; water quality parameters; and fish survival and yield in catfish culture ponds using a randomized complete block design. The estimated half‐life of fluridone in the individual ponds ranged from 1.6 d to 10.8 d. Free copper ion activity in ponds treated with copper sulphate was dynamic, ranging from pCu of 7.7 to 8.9 after each application and decreasing to approximately 12 (1 × 10 −12  M) within 1 wk after each application, approaching observed values in control ponds (pCu = 12.3–13.4). No difference in macrophyte biomass was observed among treatments. Fluridone and copper treatments elicited different responses within the phytoplankton community. Copper treatments reduced Cyanophyta biomass but increased biomass of more tolerant taxa among the Chlorophyta and Chrysophyta. Fluridone treatments reduced total phytoplankton biomass including Cyanophyta and increased the sensitivity of Chlorophyta and Chrysophyta to copper. Copper also affected zooplankton community composition as a result of direct toxic effects on sensitive zooplankton taxa (e.g., Cladocera), whereas Copepoda biomass in copper‐treated ponds exceeded that in controls. Catfish survival and yield were not significantly different among treatments. The results of the present study suggest that fluridone and copper interact at realistic application rates, increasing the ability to control algae compared with treatments where they are applied alone. Environ Toxicol Chem 2016;35:1183–1194. © 2015 SETAC